2015
DOI: 10.1089/cyber.2015.0334
|View full text |Cite
|
Sign up to set email alerts
|

Sexting Among Married Couples: Who Is Doing It, and Are They More Satisfied?

Abstract: This study examined the prevalence and correlates of sexting (i.e., sending sexual messages via mobile phones) within a sample of married/cohabiting couples (180 wives and 175 husbands). Married adults do sext each other, but it is much less common than within young adult relationships, and consists mainly of sexy or intimate talk (29% reported engaging in sexy talk with partners) rather than sexually explicit photos or videos (12% reported sending nude or nearly-nude photos). Sending sexy talk messages was po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 26 publications
4
34
0
4
Order By: Relevance
“…There is an increase in research aimed at identifying the relationship between modern technologies, romantic relationships (Drouin & Landgraff, 2012;Weisskirch & Delevi, 2011) and sexual behaviors (Gordon-Messer, Bauermeister, Grodzinski, & Zimmerman, 2013;McDaniel & Drouin, 2015;National Campaign to Prevent Teen and Unplanned Pregnancy e NCPTUP, 2008;Weisskirch & Delevi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increase in research aimed at identifying the relationship between modern technologies, romantic relationships (Drouin & Landgraff, 2012;Weisskirch & Delevi, 2011) and sexual behaviors (Gordon-Messer, Bauermeister, Grodzinski, & Zimmerman, 2013;McDaniel & Drouin, 2015;National Campaign to Prevent Teen and Unplanned Pregnancy e NCPTUP, 2008;Weisskirch & Delevi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As electronic sexual communication has become more commonplace, researchers have explored the positive and negative correlates and outcomes of sexting. Overall, these studies have shown that sexting more frequently in relationships is related to sexual satisfaction [ 42 ], and in some cases, relationship satisfaction [ 40 , 43 , 44 , 45 ]; however, sexting is also related to myriad of negative correlates, including conflict, ambivalence, and insecure attachment patterns [ 42 ]. Moreover, and more relevant to the current inquiry, sexting, especially unwanted or coerced sexting, has been found to relate to negative psychological symptoms, dating violence, offline sexual coercion, and IPA e.g., [ 34 , 35 , 42 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some data suggest that individuals perceive sexting as a way to continue to connect in a relationship, particularly during college when partners may be separated [ 10 , 40 , 41 ]. Additionally, researchers have shown that sexting is associated with increased sexual satisfaction [ 42 ] and relationship satisfaction [ 40 , 43 , 44 , 45 ], though this may vary as a function of attachment style and gender. Recent latent profile analyses involving Americans and Canadians in cohabiting relationships [ 42 ], however, showed that nonsexters did not differ from those who sexted often (frequent and hypersexters) on relationship satisfaction, and sexters also fared worse in terms of other relationship markers, such as conflict, ambivalence, and attachment security.…”
Section: Introductionmentioning
confidence: 99%
“…En el modelo, se metió la satisfacción con la relación, al ser un aspecto esencial en el estudio de las parejas (González et al, 2009;Romero et al, 2008). Además, se incluyó una variable de personalidad, la búsqueda de sensaciones sexuales, que por su naturaleza puede actuar como un factor de riesgo de infi delidad sexual (McDaniel & Drouin, 2015;Zheng & Zheng, 2014). El modelo indica que fomentar una buena relación, una personalidad reacia a la búsqueda de sensaciones sexuales y una actitud favorable a la exclusividad marital previenen el deseo y la conducta de infi delidad sexual.…”
Section: Discussionunclassified
“…Se hipotetiza que la infi delidad sexual sea predicha por el deseo de infi delidad sexual (Jackman, 2015;Romero et al, 2007); el deseo sea pronosticado por una actitud favorable hacia la infi delidad a la pareja (ATMES), insatisfacción con la pareja y la búsqueda de sensaciones sexuales y la actitud favorable hacia la infi delidad sea predicha por menor satisfacción marital y mayor búsqueda de sensaciones sexuales (Birnbaum et al, 2014;González, Martínez-Taboas, & Martínez, 2009;Romero, Cruz, & Díaz-Loving, 2008). Además, se espera una correlación negativa entre estas dos últimas variables (McDaniel & Drouin, 2015;Zheng & Zheng, 2014). Este modelo hipotético se diagrama en la fi gura 1.…”
Section: Planteamiento Del Estudiounclassified